2019
DOI: 10.1590/0001-376520182018762
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of 16S rRNA methyltransferase in Brazil: RmtG in Klebsiella aerogenes ST93 (CC4)

Abstract: Aminoglycosides are a class of antibiotics that play a key role in antimicrobial treatment of Multidrug resistant (MDR) Gram-negative bacilli, typically in combination with β-lactams. Ribosomal 16S RNA modification by methyltransferases (e.g. RmtG) is an aminoglycoside resistance mechanism that, along with the occurrence carbapenem-resistant enterobacteriaceae (CRe), has become a clinical concern. In Brazil, rmtg genes were initially reported in Klebsiella pneumoniae, and monitoring isolates from other species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…At present, the rmtG gene was still mainly prevalent in South America, especially in K. pneumoniae isolated from Brazil. It also could be found in K. aerogenes, P. aeruginosa, and E. coli isolated in America, India, Switzerland [ 3 , 59 , 96 , 97 , 98 , 100 , 101 ]. However, no strain carrying rmtG has been found in China so far.…”
Section: Plasmid-mediated 16s Rrna Methylase Resistance Gene and Its ...mentioning
confidence: 99%
“…At present, the rmtG gene was still mainly prevalent in South America, especially in K. pneumoniae isolated from Brazil. It also could be found in K. aerogenes, P. aeruginosa, and E. coli isolated in America, India, Switzerland [ 3 , 59 , 96 , 97 , 98 , 100 , 101 ]. However, no strain carrying rmtG has been found in China so far.…”
Section: Plasmid-mediated 16s Rrna Methylase Resistance Gene and Its ...mentioning
confidence: 99%
“…The results also indicate that 11 ST93 isolates and 9 ST56 were clustered into one separate sub-cluster, respectively, which exhibited a slight difference in the core genome sequence. Recent studies found that ST93 was the most prevalent clone in the global K. aerogenes genome database, which indicated that ST93 might be dominant sequence type global clones in clinical settings [13,39]. Furthermore, the emergence of fecal carriage and human infection MDR K. aerogenes isolates resistant to multiple antibiotics, especially resistant to carbapenems is considered a substantial threat to public health [17,40].…”
Section: Whole Genome Sequencing and Comparison Analysismentioning
confidence: 99%
“…Antibiotics have proved to be highly effective in treating a number of human infections and a preventative method for a variety of clinical treatments [12]. Antibiotic resistance is accelerated by the extensive and frequently ineffective use of antibiotics [13,14]. K. aerogenes isolates that harbor an extended range of beta-lactamase and carbapenemase genes and such strains are frequently associated with hospital outbreaks [15].…”
Section: Introductionmentioning
confidence: 99%